2021
DOI: 10.1186/s43058-021-00212-y
|View full text |Cite
|
Sign up to set email alerts
|

Integrating social determinants of health screening and referral during routine emergency department care: evaluation of reach and implementation challenges

Abstract: Background Despite the importance of social determinants in health outcomes, little is known about the best practices for screening and referral during clinical encounters. This study aimed to implement universal social needs screening and community service referrals in an academic emergency department (ED), evaluating for feasibility, reach, and stakeholder perspectives. Methods Between January 2019 and February 2020, ED registration staff screene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
62
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(64 citation statements)
references
References 31 publications
2
62
0
Order By: Relevance
“…Focus on implementation strategies to address gaps in reach and adoption is needed. 15 - 17 ,33,34 Implementation science offers investigators frameworks through which the necessary implementation strategies and measures can be systematically identified to impact both screening uptake and patient capture. 15 , 35 , 36 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Focus on implementation strategies to address gaps in reach and adoption is needed. 15 - 17 ,33,34 Implementation science offers investigators frameworks through which the necessary implementation strategies and measures can be systematically identified to impact both screening uptake and patient capture. 15 , 35 , 36 …”
Section: Discussionmentioning
confidence: 99%
“…Studies that used the RE-AIM framework to examine HRSN screening implementation found screening was limited in its reach 15 , 16 and insured patients were more likely to undergo screening. 16 Our study found similar results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is unlikely that data collected through this mechanism will be representative of a community’s FI status as many of those who experience FI are also those experiencing barriers to accessing health services. Further, data suggest that the social stigma associated with FI and other social determinants may limit the ability to understand the problem during healthcare encounters, apply for federal programs, and seek information about available resources [ 48 , 49 ].…”
Section: Introductionmentioning
confidence: 99%
“…6,[13][14][15] Lessons learned from pediatric and adult emergency medicine social care networks suggest that effective and sustainable strategies recognize these physician-level limitations in pursuit of organizational solutions. 3,[16][17][18][19][20] In the ED, these macrolevel interventions, or organizational factors, aim to operationalize social risk awareness and assistance by integrated workflow approaches, community referral databases, and leveraging social work services. 5,19 In this study, our purpose was to assess the association between health care organizational factors and PEM physician social care perception and practices among PEM PDs and fellows in the United States.…”
Section: Introductionmentioning
confidence: 99%